Review of Epigenetics of Folate and Associated Derangements - Ahmad, K. A.; Wurochekke, A. U. (Darul Yasin Al Sys, 2025)
Folate, a vital water-soluble B vitamin, plays a central role in one-carbon metabolism, serving as a key donor of methyl groups necessary for DNA methylation—an essential epigenetic mechanism regulating gene expression. This review synthesizes current evidence on folate's role in epigenetic modulation, drawing from PubMed, Google Scholar, and other reputable sources. Particular attention is given to folate’s inverse association with cancer risk, especially colorectal cancer, and its influence on epigenetic processes such as DNA methylation and histone modifications. Dysregulation of these mechanisms is closely linked to carcinogenesis and other chronic non-communicable diseases. Moreover, mutations or deficiencies in folate-related proteins may result in aberrant epigenetic reprogramming, leading to altered transcriptional activity and increased disease susceptibility. This review underscores the critical importance of adequate folate status in maintaining epigenetic homeostasis and preventing the onset of various malignancies and chronic conditions.